Uptake of occupational safety and health management systems in manufacturing industry of Zimbabwe: case of Mutare manufacturing factories - Mandowa, Johanes; Matsa, Mark; Jerie, Steven (Frontiers in Environmental Health, 2025)
BackgroundPromotion of OSH management systems (OSHMSs) has gained commendable traction worldwide with the developed world taking the lead, however non to suboptimal implementation of OSHMSs is still evident in the least developed and developing countries. The purpose of this study was to evaluate the uptake of OSHMSs in the manufacturing industry of the City of Mutare in Zimbabwe.MethodsA descriptive cross-sectional study that exploited the pragmatism philosophical approach was utilized. Data collection was done through administration of 312, 30 and 11 questionnaires to worker, top manager and OSH practitioner respondents respectively complimented by interviews and secondary data from respective manufacturing factories. Data was analyzed, presented using pie charts, bar graphs and frequency tables to illustrate trends and then discussed qualitatively in continuous prose.ResultsResults revealed subdued implementation of OSHMSs in manufacturing industry of Mutare as evidenced by a low uptake rate of 26.7%. Results projected lack of leadership and management commitment and lack of human, material, and financial resources for systems sustenance as main reasons for non-implementation of OSHMSs.ConclusionLow uptake rate of OSHMSs revealed is a serious bottleneck to the endeavor to attain OSH sustainability for securing the future of work.